Penggunaan Karbon Aktif Dari Bahan Alam Untuk Menyisihkan Logam Besi (Fe) - Tania Octalina Tamamy; Lita Darmayanti; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Agricultural waste is very likely to be used as activated carbon. This is because the waste is very much and wasted. The impact of the large amount of agricultural waste produced has the potential to pollute the environment. One of the efforts made to utilize waste and increase its economic value is to process it into an active circuit which is then applied as an adsorbent. Therefore, this article will present a brief review of activated carbon from natural materials for the potential of metal (Fe). Keywords : active carbon, adsorption, ion Fe consentration